The effectiveness of legislative reforms in the protection of public property in Iraq - جعفر, رشا محمد (Journal of Legal Sciences, 2019)
Public property has been very important because the function of the state is not limited to traditional jobs, but extends to all aspects of activities to provide services to the public, with the attendant use of public property and the need to maintain it as the basis for such activities.The legislation concerned the Public property and its protection. Starting with the Constitution, which is the highest legal rules in the state as well as general laws administrative decisions.This study aims to shed light on the concept of legislative reforms and its effects on legislation that protects the Public property, which is a precise legislative process that needs to be examined because it does not always aim at evaluating the course of the legislation, which negatively affects the protection available. Statement of reforms that concern the protection of state funds, and have achieved the purpose of the street behind the adoption?.The existence of a lot of contradiction between the provisions of the laws that concern the protection of Public property and the provisions of the current articles of the Constitution of  2005 raises many problems and questions about their treatment.